Dependence of property incomes and social contributions as indicators of agro-budgetary policy management - Pantić Nemanja; Milunović Milan; Tankosić Mirjana; Marjanović Nataša; Krstić Snežana (Ekonomika Poljoprivrede (1979), 2019)
Agro-budget policy is the basic lever of modern fiscal theory. For this reason, it is scientifically challenging for all market economies, but also for countries in transition. Agro-budget deficits and amounts of public debts faced by many countries requires orientation on this policy. Harmonization of economic policies, inter alia, tax rates, is a necessity but difficulties in its realization are numerous. Numerous authors emphasize its necessity, but also the need to investigate the correlation of categories of government revenues. This article is based on determining the dependence between property incomes and social contributions and the obtained results will confirm or reject hypotheses. In addition, obtained results will show the degree of development of budget policy and thus agrobudget policy and leave space for future authors to find appropriate measures and instruments in future researches for achieving basic macroeconomic goals.